PECULIARITIES OF LEGAL REGULATION IN THE FIELD OF EMERGENCY PROTECTION OF THE REPUBLIC OF UZBEKISTAN - Esenbaev Djanibek Tairovich (Western European Studies, 2024)
This article is widely analyzed on the basis of national and foreign legal norms in this article. The specifics of the legal regulation of emergencies were studied on the basis of the views of scientists.
Keywords: Emergencies; civil protection; emergency right